2016
DOI: 10.1007/s40273-015-0380-x
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars: How Can Payers Get Long-Term Savings?

Abstract: The term ‘biosimilar’ refers to an alternative similar version of an off-patent innovative originator biotechnology product (the ‘reference product’). Several biosimilars have been approved in Europe, and a number of top-selling biological medicines have lost, or will lose, patent protection over the next 5 years. We look at the experience in Europe so far. The USA has finally implemented a regulatory route for biosimilar approval. We recommend that European and US governments and payers take a strategic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 18 publications
2
77
0
10
Order By: Relevance
“…This study showed that the number of incentive policies dedicated to enhance biosimilar uptake is an important driver of biosimilar penetration, as already suggested in qualitative studies [16,17,39,40]. The opposite would have been surprising and would have questioned the face validity of the results or the effectiveness of such policies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This study showed that the number of incentive policies dedicated to enhance biosimilar uptake is an important driver of biosimilar penetration, as already suggested in qualitative studies [16,17,39,40]. The opposite would have been surprising and would have questioned the face validity of the results or the effectiveness of such policies.…”
Section: Discussionsupporting
confidence: 63%
“…One study estimated the impact of biosimilar entry in terms of healthcare systems savings between 2007 and 2020 for eight EU countries (France, Germany, Italy, Poland, Romania, Spain, Sweden, and the UK), ranging from €11.8 billion to €33.4 billion [12]. Other qualitative studies assessed the levers and barriers to the uptake of biosimilars based on analysis of biosimilar uptake, price reduction, and various policies implemented across EU MS [2,8,[13][14][15][16][17] One quantitative study (Rovira et al [18]) assessed market dynamics of biosimilars in 24 EU MS, as well as Norway and Switzerland, between 2007 and 2010 using bivariate regression, and reported faster launch of biosimilars after marketing authorisation, associated to countries' gross national income and expenditure on health, pharmacists' generics substitution (inversely), and medicines' price level index. A recent survey providing an overview of pricing and reimbursement policy approaches across Europe for biological medicines, and specifically applied to biosimilars showed heterogeneity in policies and their implementation between the different countries [11].…”
Section: Background and Objectivementioning
confidence: 99%
“…Biosimilars should be distinguished from generics, especially in terms of higher development costs, owing to the complexity and high cost of the manufacturing process, and different development requirements [48,119]. Despite significant differences between biosimilar and generic markets, similar trends have been observed with regard to the factors potentially influencing generic and biosimilar uptake.…”
Section: Discussionmentioning
confidence: 99%
“…IRP, ERP, tendering, and mandatory price linkage) in general seem to limit the penetration of biosimilars in the long term, despite short-term savings. In contrast, demand-side policies are considered to impact uptake positively [119][120][121][122][123][124].…”
Section: Discussionmentioning
confidence: 99%
“…Policies to encourage the uptake of biosimilars differ from policies to encourage to uptake of generic medicines because of the perception that biosimilar medicines should not be treated as 'generics' [116]. For instance, prices of biosimilars are linked to originator prices, the required difference between the biosimilar and the originator price is lower compared to generics (e.g., 30% for generics and 15% for biosimilars in Croatia; and 50% for generics and 30% for biosimilars in Lithuania) [117].…”
Section: Biosimilar Medicines' Policiesmentioning
confidence: 99%